A Case of a Persistent Postoperative Infection Caused by Multidrug-Resistant Kluyvera ascorbata in the Oral and Maxillofacial Region - Si-Hai Zou; Lu-Ying Zhu; Yong Li; Fu-Gui Zhang (Case Reports in Infectious Diseases)
Introduction. Kluyvera ascorbata infection is rare, but it has been extensively studied because of its potential to cause a wide range of infections and its ability to transfer the gene encoding for CTX-M-type extended spectrum β-lactamases (ESBLs) to other Enterobacteriaceae. Case Presentation. The authors report a case of a 61-year-old Chinese male with a persistent postoperative infection caused by a multidrug-resistant ESBL-producing K. ascorbata. Following antimicrobial susceptibility testing, he was aggressively treated with gentamicin and levofloxacin with a favorable outcome. Conclusion. To our knowledge, this is the first case report of a persistent postoperative infection caused by a multidrug-resistant K. ascorbata in the oral and maxillofacial region. The authors suggest that K. ascorbata infection warrants prompt identification and aggressive antibiotic management, given that ESBL-producing K. ascorbata is resistant to penicillins and first-generation to third-generation cephalosporins.